Help-Seeking Self-Stigma and the Association Between Perceived Social Support and Psychological Distress Among Kuwait University Students: An Exploratory Cross-Sectional Moderation Analysis - Fatima Al-Ghadban; Ahmad Salman (European Journal of Investigation in Health, Psychology and Education, 2026)
Background: Perceived social support is consistently associated with lower psychological distress among university students, but the strength of this association may vary. We examined whether help-seeking self-stigma modifies it. Methods: In a cross-sectional online survey, 507 Kuwait University students completed the Patient Health Questionnaire-4 (PHQ-4), the Multidimensional Scale of Perceived Social Support (MSPSS) and the Self-Stigma of Seeking Help Scale (SSOSH). Hierarchical linear regression tested the perceived support × self-stigma interaction, adjusting for age, sex, nationality and year of study; SSOSH structure was examined by confirmatory factor analysis. Results: Of 507 eligible students (80.9% female; mean age = 21.4 years, SD = 4.4), 458 had complete PHQ-4 data. The inverse association between perceived support and distress weakened as self-stigma increased (B = 0.003, 95% CI 0.001–0.005, p = 0.007; p = 0.040 with heteroscedasticity-consistent standard errors; ΔR2 = 0.015) and was not detectable at high self-stigma. The Arabic SSOSH was not unidimensional: positively and reverse-worded items formed uncorrelated factors (r = −0.01), and the interaction was carried by the reverse-worded items. Conclusions: Help-seeking self-stigma may index variation in this association, but the finding is exploratory and constrained by the measurement properties of the SSOSH in this population.